The effect of albendazole treatment on non-seizure outcomes in patients with symptomatic neurocysticercosis. (22nd March 2018) - Thapa, Kriti; Romo, Matthew L; Carpio, Arturo; Leslie, Denise; Andrews, Howard; Hauser, W Allen; Kelvin, Elizabeth A
Abstract: Background: There is little information about the impact of anthelminthic treatment on clinical symptoms other than seizures in neurocysticercosis (NC). We investigated the effect of albendazole on non-seizure symptoms experienced by patients with NC. Methods: Data are from a randomized controlled trial comparing albendazole plus prednisone with placebo plus prednisone for treatment of NC among 173 patients with active or transitional NC cysts and new-onset symptoms. We performed negative binomial regression to examine the number of follow-up visits when a symptom was reported, logistic regression to examine the probability of experiencing the symptom and Cox proportional hazards models to examine the time to first reporting the symptom. Results: Eighty-five percent of patients reported at least one non-seizure symptom at baseline. Those treated with albendazole had significantly lower odds of memory loss and/or confusion during months 1–24 (odds ratio [OR] 0.42, p=0.037) and significantly increased odds of anxiety and/or depression during months 1–12 (OR 1.87, p=0.049). No treatment difference existed in experiencing symptoms in general or in experiencing headaches, limb weakness or gait disturbances, vomiting, nausea and/or stomach pain or visual disturbances over the follow-up period. Conclusions: While the prevalence of non-seizure symptoms was high, albendazole treatment was associated with only two significant differences in the non-seizure symptoms over follow-up. Further research is needed to identify strategies to reduce the long-term symptom burden in patients with NC.